THE EFFECT OF ICT ADOPTION ON THE PERFOMANCE OF HEALTH SECTOR IN KENYA: ASURVEY OF HOSPITALS IN NAIROBI COUNTY - Mukuna, Njau (International Journal of Technology and Systems, 2016)
Purpose: The purpose of the study was to establish the effect of the effect of ICT adoption on the performance of health sector in Kenya: a survey of hospitals in Nairobi County. Methodology: Therefore, this study attempted to use descriptive research design to report the status quo of the ICT and its effect on performance of hospitals .The study targeted a population of all the hospitals in Nairobi County. According to the NHIF website, there are 52 hospitals in Nairobi County As at 1st JAN2011, this comprised the population of the study. The researcher used 20 % of the 52 Hospitals. The sample size was therefore 10 hospitals. The 10 hospitals were selected through random sampling. Three departments (finance and administration, human resource, ICT department) were used for stratification an identification of the respondents. Only three questionnaires was issued to each selected department. This gave rise to 90 respondents In this study primary data was collected using a structured questionnaire. The data collected was analyzed by use of descriptive statistics. The data analysis was through simple tabulation and presentation of report generated from spreadsheets such as excel. In addition, the Statistical Package for Social Sciences (SPSS) was used to generate the frequencies and percentages that were used for excel tabulations. The data was presented using data tables and charts Results: The study concluded that adoption and effective use of ICT in hospitals, contributed positively to the performance of such hospitals. It was also possible to conclude that use of adequate computers, phones and internet facilities has contributed positively to the performance of hospitals. The study also concludes that adoption of good record keeping and management system has contributed positively towards the hospital performance. Finally, the study concludes that ensuring an accounting and information management system and use of qualified and trained ICT staff yielded positively to the performance of hospitals using ICT in their operations. Unique contribution to theory, practice and policy: Following the study results, it was recommended that for hospitals to yield better profits, it is important to adopt the use of ICT in their operations. For instance the management should emphasize on use of adequate computers, phones and internet facilities. The study also recommends the management to adopt good record keeping and management system.The study recommends that the management should ensure accounting and information management system are emphasized in usage and ensure that training is emphasized so as to make use of qualified and trained ICT staff.